Form for reporting Iowa Christmas bird counts to Iowa Bird Life, W. Ross Silcock, December 20, 1987 - Silcock, W. Rosset al (1987)
Iowa Christmas bird counts of regular and uncommon species found in Fremont County, Nebraska and Missouri contributed by W. Ross Silcock, December 20, 1987. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1987-1988. Epson - sheet feed